Hubungan Karakteristik Bidan Dengan Mutu Pelayanan Antenatal Care Berdasarkan Standar Operasional Prosedur Di Wilayah Kerja Puskesmas Mantingan Kabupaten Ngawi - Abu, Aliah Dwi Kurnia Haji, Yuli Kusumawati, SKM., M. Kes (Epid), Kusuma Estu Werdani, SKM., M.Kes (2015)
The scope of first visiting (K1) and fourth visiting (K4) in the clinic of Mantingan has bad servicing, one of the problem is the antenatal care is not appropriate with the standard operation procedure. The purpose of this research to know the correlation of midwife characteristic with quality servicing of antenal care based on the standard operation procedure in the clinic of Mantingan area Kabupaten Ngawi. The method of this research used survey observational design by using cross sectional approach. The population of this research is all midwife in the clinic of Mantingan and the total number of sample is 30 persons. Statistic examining uses correlation Pearson of Product moment and Anova statistic by using SPSS 17. The result of the research shows that the variable of quality servicing antenal care is old (r=0,445) p value (0,014),working experience period (r=0,401) and experience (r=0,474) p value (0,028), so there is no correlation of the quality survicing with the employee status (F=0,768) p value (0,474). It is expected that the state official of wealthy of Kabupaten Ngawi will give the survicing workshop of antenatal care by using the new standard for it's implementating.